AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA MASA PANDEMI COVID-19 - Suci Aprilia; Zubaidah R; Dona Fitriawan (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to find out how students' learning activities in learning mathematics during the covid-19 pandemic at SMK Negeri 03 Pontianak. The research method used is descriptive with the type of qualitative research. The research subjects were 37 students of class XI Accounting 2 who took part in mathematics lessons during the covid-19 pandemic. The results of data analysis showed that student learning activities in learning mathematics during the pandemic at SMK Negeri 03 Pontianak were in the